Unemployment in Planned and Capitalist Economies: Comment - Holzman, F. D. (Quarterly Journal of Economics, 1955)
Journal Article Unemployment in Planned and Capitalist Economies: Comment Get access F. D. Holzman F. D. Holzman University of Washington, Seattle Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 69, Issue 3, August 1955, Pages 452–460, https://doi.org/10.2307/1885851 Published: 01 August 1955